Application Of Recapitulation And Staff Performance Assessment Using Standard Working Method - Agustia Hananto; Eko Pramono; Baenil Huda (Buana Information Technology and Computer Sciences (BIT and CS), 2022)
Employee performance evaluation or appraisal is needed to assess company employees' work achievement or work performance against the given target within a specific time. The purpose of the study was to analyze the method of recapitulation and staff performance appraisal and create a design model for the application of recapitulation and staff performance appraisal. The research method used is qualitative research, where data collection is done using observation and interviews. Application development based on the iterative waterfall method accommodates the recapitulation process and employee performance appraisal. The benefits of the research carried out are to determine the impact of information delays and speed up the recapitulation process and the performance appraisal itself. Every month, information regarding work achievements is presented in an application that each employee can see. The final results of the recapitulation and assessment in the form of total values and ratios of work achievement are expected to facilitate the head of the department in making decisions